Addressing Significant Weather Impacts on Airports: Quick Start Guide and Toolkit - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
TRB's Airport Cooperative Research Program (ACRP) Report 160: Addressing Significant Weather Impacts on Airports provides a web toolkit that raises airport operator awareness about vulnerabilities caused by significant weather events. The toolkit helps airports develop more robust contingency and recovery plans, in addition to their airport emergency plans. This toolkit focuses on events that are “rare but plausible”; that is, events that may have happened in the distant past, or in adjacent geographic areas, but are not common event types at the airport itself, and therefore may not be in the forefront of the airport managers’ minds. The Quick Start Guide provides guidance for using the toolkit.Disclaimers: The opinions and conclusions expressed or implied in this material are those of the researchers who performed the research. They are not necessarily those of the Transportation Research Board, the Academies, or the program sponsors. Materials noted with an asterisk (*) have been edited by TRB; otherwise, materials are as supplied by the contractor.Any digital files or software included is offered as is, without warranty or promise of support of any kind either expressed or implied. Under no circumstance will the National Academy of Sciences or the Transportation Research Board (collectively “TRB”) be liable for any loss or damage caused by the installation or operation of this product. TRB makes no representation or warranty of any kind, expressed or implied, in fact or in law, including without limitation, the warranty of merchantability or the warranty of fitness for a particular purpose, and shall not in any case be liable for any consequential or special damages.
Keywords: Transportation and Infrastructure

SBIR/STTR at the Department of Energy - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
The Small Business Innovation Research (SBIR) program is one of the largest examples of U.S. public-private partnerships, and was established in 1982 to encourage small businesses to develop new processes and products and to provide quality research in support of the U.S. government’s many missions. The Small Business Technology Transfer (STTR) Program was created in 1992 by the Small Business Research and Development Enhancement Act to expand joint venture opportunities for small businesses and nonprofit research institutions by requiring small business recipients to collaborate formally with a research institution. The U.S. Congress tasked the National Research Council with undertaking a comprehensive study of how the SBIR and STTR programs have stimulated technological innovation and used small businesses to meet federal research and development needs, and with recommending further improvements to the programs. In the first round of this study, an ad hoc committee prepared a series of reports from 2004 to 2009 on the SBIR and STTR programs at the five agencies responsible for 96 percent of the programs’ operations -- including the Department of Energy (DoE). Building on the outcomes from the first round, this second round presents the committee’s second review of the DoE SBIR program’s operations.
Keywords: Industry and Labor

Commercial Motor Vehicle Driver Fatigue, Long-Term Health, and Highway Safety: Research Needs - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
There are approximately 4,000 fatalities in crashes involving trucks and buses in the United States each year. Though estimates are wide-ranging, possibly 10 to 20 percent of these crashes might have involved fatigued drivers. The stresses associated with their particular jobs (irregular schedules, etc.) and the lifestyle that many truck and bus drivers lead, puts them at substantial risk for insufficient sleep and for developing short- and long-term health problems. Commercial Motor Vehicle Driver Fatigue, Long-Term Health and Highway Safety assesses the state of knowledge about the relationship of such factors as hours of driving, hours on duty, and periods of rest to the fatigue experienced by truck and bus drivers while driving and the implications for the safe operation of their vehicles. This report evaluates the relationship of these factors to drivers’ health over the longer term, and identifies improvements in data and research methods that can lead to better understanding in both areas.
Keywords: Transportation and Infrastructure; Health and Medicine

Developing a National STEM Workforce Strategy: A Workshop Summary - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
The future competitiveness of the United States in an increasingly interconnected global economy depends on the nation fostering a workforce with strong capabilities and skills in science, technology, engineering, and mathematics (STEM). STEM knowledge and skills enable both individual opportunity and national competitiveness, and the nation needs to develop ways of ensuring access to high-quality education and training experiences for all students at all levels and for all workers at all career stages.
Keywords: Education

Promising Practices for Strengthening the Regional STEM Workforce Development Ecosystem - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
U.S. strength in science, technology, engineering, and mathematics (STEM) disciplines has formed the basis of innovations, technologies, and industries that have spurred the nation's economic growth throughout the last 150 years. Universities are essential to the creation and transfer of new knowledge that drives innovation. This knowledge moves out of the university and into broader society in several ways – through highly skilled graduates (i.e. human capital); academic publications; and the creation of new products, industries, and companies via the commercialization of scientific breakthroughs. Despite this, our understanding of how universities receive, interpret, and respond to industry signaling demands for STEM-trained workers is far from complete. Promising Practices for Strengthening the Regional STEM Workforce Development Ecosystem reviews the extent to which universities and employers in five metropolitan communities (Phoenix, Arizona; Cleveland, Ohio; Montgomery, Alabama; Los Angeles, California; and Fargo, North Dakota) collaborate successfully to align curricula, labs, and other undergraduate educational experiences with current and prospective regional STEM workforce needs. This report focuses on how to create the kind of university-industry collaboration that promotes higher quality college and university course offerings, lab activities, applied learning experiences, work-based learning programs, and other activities that enable students to acquire knowledge, skills, and attributes they need to be successful in the STEM workforce. The recommendations and findings presented will be most relevant to educators, policy makers, and industry leaders.
Keywords: Education

Summary of Federal Law Restricting Use of Highway Safety Data in Tort Litigation - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
TRB's National Cooperative Highway Research Program (NCHRP) Legal Research Digest 72: Summary of Federal Law Restricting Use of Highway Safety Data in Tort Litigation explores the origins and provisions of 23 U.S.C. § 409, Discovery and Admission as Evidence of Certain Reports and Surveys, which prohibits the use, in tort litigation, of highway safety data created for purposes related to safety improvements on roads qualifying for federal safety improvement funding. The digest explores the amendments to the law, development of caselaw interpreting and applying the law, a 2003 Supreme Court decision, and current interpretation and application issues.
Keywords: Transportation and Infrastructure

STTR: An Assessment of the Small Business Technology Transfer Program - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
Today's knowledge economy is driven in large part by the nation's capacity to innovate. One of the defining features of the U.S. economy is a high level of entrepreneurial activity. Entrepreneurs in the United States see opportunities and are willing and able to assume risk to bring new welfare-enhancing, wealth-generating technologies to the market. Yet, although discoveries in areas such as genomics, bioinformatics, and nanotechnology present new opportunities, converting these discoveries into innovations for the market involves substantial challenges. The American capacity for innovation can be strengthened by addressing the challenges faced by entrepreneurs. Public-private partnerships are one means to help entrepreneurs bring new ideas to market. The Small Business Technology Transfer (STTR) and the Small Business Innovation Research (SBIR) program form one of the largest examples of U.S. public-private partnerships. In the SBIR Reauthorization Act of 2000, Congress tasked the National Research Council with undertaking a comprehensive study of how the SBIR program has stimulated technological innovation and used small businesses to meet federal research and development needs and with recommending further improvements to the program. When reauthorizing the SBIR and STTR programs in 2011, Congress expanded the study mandate to include a review of the STTR program. This report builds on the methodology and outcomes from the previous review of SBIR and assesses the STTR program.
Keywords: Industry and Labor

Long-Term Bridge Performance Committee Letter Report: July 5, 2016 - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
On July 5, 2016, TRB’s Long-Term Bridge Performance (LTBP) Committee sent its seventh letter report to Gregory Nadeau, administrator of the U.S. Federal Highway Administration (FHWA). The committee provides advice and assistance on the conduct of the LTBP program, which is designed to collect research-quality data on a large representative sample of in-service U.S. highway bridges and to analyze these data to improve understanding of the mechanisms and timing of bridge deterioration due to the effects of age, materials, traffic, and weather.The report includes recommendations to finalize, adopt, and implement the LTBP Business Plan; add to the Business Plan how deterioration and life-cycle cost modeling methodologies will be calibrated and used; define the research results and products that LTBP will deliver so that state agencies can ascertain what they may be required to develop in order to use these products; include in further live demonstrations of the LTBP Bridge Portal more specific queries that show state agencies the benefits of using the portal to access NDE and inspection data; and develop a plan for simplifying the use of the portal as a source of information concerning the LTBP program and the highway bridges being studied.Additionally, the report recommends that LTBP focus on steel girders as the next step in LTBP research and consider also proceeding where feasible to study treated decks (all overlays except for asphalt); reinstate, as soon as the necessary protocols are developed, research addressing asphalt overlays on bridge decks; conduct audience-specific webinars highlighting the benefits to be derived from the program be developed; delineate, prioritize, and quantify LTBP's activities and develop contingency plans for continuation of the program at high, medium, and low levels of funding reduction; expand LTBP's outreach activity to include more information about what has been accomplished and what has been planned, including information about the LTBP Bridge Portal and the WIM pooled fund partnership.
Keywords: Transportation and Infrastructure

Barriers and Opportunities for 2-Year and 4-Year STEM Degrees: Systemic Change to Support Students' Diverse Pathways - National Academy of Engineering; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
Nearly 40 percent of the students entering 2- and 4-year postsecondary institutions indicated their intention to major in science, technology, engineering, and mathematics (STEM) in 2012. But the barriers to students realizing their ambitions are reflected in the fact that about half of those with the intention to earn a STEM bachelor's degree and more than two-thirds intending to earn a STEM associate's degree fail to earn these degrees 4 to 6 years after their initial enrollment. Many of those who do obtain a degree take longer than the advertised length of the programs, thus raising the cost of their education. Are the STEM educational pathways any less efficient than for other fields of study? How might the losses be "stemmed" and greater efficiencies realized? These questions and others are at the heart of this study.
Keywords: Education

Runway Protection Zones (RPZs) Risk Assessment Tool Users’ Guide - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
TRB's Airport Cooperative Research Program (ACRP) Research Report 168: Runway Protection Zones (RPZs) Risk Assessment Tool Users’ Guide helps airport operators evaluate the risk of an aircraft accident within an RPZ. Although runway protection zones (RPZs) are supposed to be clear of structures and people, it is still common for activities to occur within an RPZ for many reasons, and these reasons can be beyond the control of the airport operator.The report is accompanied by a tool used to assess the risk of an aircraft accident within the RPZ, and, based on that output, assess the risk to people and property, considering the population density and land use. The tool can be used to run scenarios for planning around an RPZ or if changes are being considered, for example a change in the threshold, extending a runway, removing a hazard, and planning for a new runway. Ideally, the Users’Guide should be read before starting to use the tool.Chapter 4 has instructions for installing the tool, including how to download SQL, which is required to run the RPZ_RAT tool. For background on the development of the tool, see the Contractor’s Final Report.Disclaimer: This software is offered as is, without warranty or promise of support of any kind either expressed or implied. Under no circumstance will the National Academy of Sciences, Engineering, and Medicine or the Transportation Research Board (collectively "TRB") be liable for any loss or damage caused by the installation or operation of this product. TRB makes no representation or warranty of any kind, expressed or implied, in fact or in law, including without limitation, the warranty of merchantability or the warranty of fitness for a particular purpose, and shall not in any case be liable for any consequential or special damages.
Keywords: Transportation and Infrastructure

Public Perception of Mileage-Based User Fees - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
TRB’s National Cooperative Highway Research Program (NCHRP) Synthesis 487: Public Perception of Mileage-Based User Fees explores proposals to replace the current motor fuel tax with a road usage charge assessed on vehicle-miles traveled, often called a mileage-base user fee (MBUF). The report identifies and assesses various measures of public opinion on the MBUF concept.
Keywords: Transportation and Infrastructure

Incident Command System (ICS) Training for Field-Level Supervisors and Staff - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
TRB's National Cooperative Highway Research Program (NCHRP) Web-Only Document 215: Incident Command System (ICS) Training for Field-Level Supervisors and Staff provides training materials and guidance for transportation field personnel to help their organizations operate safely in an emergency or traffic management event. This course is intended to review the basic ICS structures and terminologies aimed to ensure safety, personnel accountability, and support for the agency’s financial reimbursement efforts.This product includes lesson plans, guidance on classroom set-up, complete slide shows with scripts or instructor prompts, instructions for creating materials, and some information about training for adults. Specifically, the materials include:1. A video presentation with voice-over of the MSPowerPoint slides for the ICS for Field-Level Transportation Supervisors and Staff training course (Format: ISO of an MP4 file)2. An Instructor Guide and Student Course Evaluation (Customizable; Format: ZIP file of Microsoft Word, Microsoft PowerPoint, PDF files).3. An Instructor Guide and Student Evaluation (Customizable; Format: ZIP file of Microsoft Word and Microsoft PowerPoint files)4. Discussion-Based Training Scenarios, which contain an instructor's guide and student evaluation (Customizable; Format: ZIP file of Microsoft Word files)5. ICS Quick Start Cards (Customizable; Format: Microsoft Word)6. A Supervisor’s Folder, which includes a materials list and construction information (Format: Microsoft Word).The course material provided in this project assumes that instructors have completed classes on delivering training to adults, have certificates in at least ICS 100, 200 and 300, and have some experience with ICS, at the field level or in an Emergency Operations Center (EOC). It is also assumed that instructors may have had experience working with a transportation agency in emergency planning or training, or as a field supervisor, and to have also completed ICS 400 and E/L449 ICS “Incident Command System Curricula TTT” courses.Disclaimer: This software is offered as is, without warranty or promise of support of any kind either expressed or implied. Under no circumstance will the National Academy of Sciences, Engineering, and Medicine or the Transportation Research Board (collectively "TRB") be liable for any loss or damage caused by the installation or operation of this product. TRB makes no representation or warranty of any kind, expressed or implied, in fact or in law, including without limitation, the warranty of merchantability or the warranty of fitness for a particular purpose, and shall not in any case be liable for any consequential or special damages.
Keywords: Transportation and Infrastructure

Eliminating the Public Health Problem of Hepatitis B and C in the United States: Phase One Report - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
Hepatitis B and C cause most cases of hepatitis in the United States and the world. The two diseases account for about a million deaths a year and 78 percent of world's hepatocellular carcinoma and more than half of all fatal cirrhosis. In 2013 viral hepatitis, of which hepatitis B virus (HBV) and hepatitis C virus (HCV) are the most common types, surpassed HIV and AIDS to become the seventh leading cause of death worldwide.
Keywords: Health and Medicine

Clean Water Act Requirements for Airports - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
TRB's Airport Cooperative Research Program (ACRP) Research Report 169: Clean Water Act Requirements for Airports describes the environmental regulations and permitting programs to which airports may be subject in their management of stormwater and other types of water resources. It covers governing federal programs; stormwater discharges associated with industrial activities, construction activities, and municipal separate storm sewer systems; process water or wastewater treatment discharges; industrial wastewater pretreatment discharges; and other relevant permit programs.
Keywords: Transportation and Infrastructure

Deriving Drug Discovery Value from Large-Scale Genetic Bioresources: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
The process of discovering and developing a new drug or therapy is extremely costly and time consuming, and recently, it has been estimated that the creation of a new medicine costs on average more than $2 billion and takes 10 years to reach patients. The challenges associated with bringing new medicines to market have led many pharmaceutical companies to seek out innovative methods for streamlining their drug discovery research.
Keywords: Health and Medicine

Highway Capacity Manual 6th Edition: A Guide for Multimodal Mobility Analysis - Transportation Research Board (The National Academies Press, 2016)
Now available to order from the TRB Bookstore, the Highway Capacity Manual, Sixth Edition: A Guide for Multimodal Mobility Analysis (HCM) provides methods for quantifying highway capacity. In its current form, it serves as a fundamental reference on concepts, performance measures, and analysis techniques for evaluating the multimodal operation of streets, highways, freeways, and off-street pathways. The Sixth Edition incorporates the latest research on highway capacity, quality of service, Active Traffic and Demand Management, and travel time reliability and improves the HCM's chapter outlines. The objective is to help practitioners applying HCM methods understand their basic concepts, computational steps, and outputs. These changes are designed to keep the manual in step with its users' needs and present times. HCM has evolved over the years to keep pace with the needs of its users and society, as the focus of surface transportation planning and operations in the United States has moved from designing and constructing the Interstate highway system to managing a complex transportation system that serves a variety of users and travel modes. Providing mobility for people and goods is transportation's most essential function. It consists of four dimensions:
Keywords: Transportation and Infrastructure

Transportation Resilience: Adaptation to Climate Change - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
Transportation Resilience: Adaptation to Climate Change and Extreme Weather Events summarizes a symposium held June 16–17, 2016 in Brussels, Belgium. The fourth annual symposium promotes common understanding, efficiencies, and trans-Atlantic cooperation within the international transportation research community while accelerating transport-sector innovation in the European Union (EU) and the United States.The two-day, invitation-only symposium brought together high-level experts to share their views on disruptions to the transportation system resulting from climate change and extreme weather events. With the goal of fostering trans-Atlantic collaboration in research and deployment, symposium participants discussed the technical, financial, and policy challenges to better plan, design, and operate the transportation network before, during, and after extreme and/or long-term climate events.
Keywords: Transportation and Infrastructure

The Future of Atmospheric Chemistry Research: Remembering Yesterday, Understanding Today, Anticipating Tomorrow - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
Our world is changing at an accelerating rate. The global human population has grown from 6.1 billion to 7.1 billion in the last 15 years and is projected to reach 11.2 billion by the end of the century. The distribution of humans across the globe has also shifted, with more than 50 percent of the global population now living in urban areas, compared to 29 percent in 1950. Along with these trends, increasing energy demands, expanding industrial activities, and intensification of agricultural activities worldwide have in turn led to changes in emissions that have altered the composition of the atmosphere.
Keywords: Earth Sciences

Future Directions for NSF Advanced Computing Infrastructure to Support U.S. Science and Engineering in 2017-2020 - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
Advanced computing capabilities are used to tackle a rapidly growing range of challenging science and engineering problems, many of which are compute- and data-intensive as well. Demand for advanced computing has been growing for all types and capabilities of systems, from large numbers of single commodity nodes to jobs requiring thousands of cores; for systems with fast interconnects; for systems with excellent data handling and management; and for an increasingly diverse set of applications that includes data analytics as well as modeling and simulation. Since the advent of its supercomputing centers, the National Science Foundation (NSF) has provided its researchers with state-of-the-art computing systems. The growth of new models of computing, including cloud computing and publically available by privately held data repositories, opens up new possibilities for NSF.
Keywords: Computers and Information Technology

Global Health Impacts of Vector-Borne Diseases: Workshop Summary - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
Pathogens transmitted among humans, animals, or plants by insects and arthropod vectors have been responsible for significant morbidity and mortality throughout recorded history. Such vector-borne diseases – including malaria, dengue, yellow fever, and plague – together accounted for more human disease and death in the 17th through early 20th centuries than all other causes combined. Over the past three decades, previously controlled vector-borne diseases have resurged or reemerged in new geographic locations, and several newly identified pathogens and vectors have triggered disease outbreaks in plants and animals, including humans.
Keywords: Health and Medicine